Use of Problem-Based Learning Strategies in Improving Problem Solving Skills - Sappaile, Baso Intang; Marito, Winanda; Satyaninrum, Ika Rahayu; Kurniawati, Hartin; Wang, Yuanyuan; Zou, Guijiao (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Education for a child is very important for motor development and his thinking becomes critical in responding to an incident. His skills can be honed properly and master skills that support his future career. So that the potential for the progress of each child can be achieved and learning objectives can be completed optimally. In life, of course, you will not be separated from various kinds of problems, so the solution to every problem must exist and be able to solve it. The problem based learning strategy is the answer to improve problem solving skills. This strategy is a problem-triggered learning model, which encourages students to learn and work cooperatively in groups to find solutions, think critically and analytically, be able to determine and use appropriate learning resources. For this reason, it is necessary to apply this method in education. The purpose of this research was to improve problem solving skills using the problem based learning (PBL) method. By maximizing this method many positive impacts will be obtained. The method used in this research is a quantitative method. The data obtained is through the distribution of a questionnaire. The questionnaire was made using the Google form application. The results of this study explain that the use of problem based learning strategies to improve problem solving skills in education can help students solve problems with the right solutions. As well as sharpening the ability to think critically and systematically, so that they can be more mature in responding to various problems. The conclusion of this study is that the use of problem-based learning strategies to improve problem-solving skills by students can be maximized, because they have mastered the right and effective way to solve a problem. The limitation of this research is that researchers only conduct this research at the school level where the method requires new strategies in learning such as the use of problem based learning strategies.